Differing processing abilities for specific face properties in mid-childhood and adulthood. - Cohen Kadosh, K (2011)
The ability to process facial information is vital for social interactions. Previous research has shown that mature face processing depends on the extraction of featural and configural face information. It has been also shown that the acquisition of these processing skills is prolonged in children. The order in which different face properties are processed is currently less understood. Namely, while some research has supported a parallel-route model which groups different properties according to their variability, other studies have shown that specific invariant properties, such as facial identity, can serve as a reference frame for interpreting more dynamic aspects, such as facial expression or eye gaze direction. The current study tested a different approach, which proposes that face property processing varies with task requirements. Sixteen adults did a same-different task where the second face could differ from the first in the identity, expression, or gaze, or any combination of those. We found that reaction times increased and accuracy rates decreased when the identity was repeated, suggesting that changes in facial identity were the most salient ones. Finally, we tested two groups of 7-to 8- and 10- to 11-year-old children and found lower accuracy rates for those face properties that rely in particular on configural information processing strategies. This suggests that while overall, face processing strategies are adult-like from 7 years of age, the processing of specific face properties develops continuously throughout mid-childhood.